Erfolgsfaktoren bei Mergers and Acquisitions – Warum schaffen Portfoliomaster mehr Value Added? - Sievers, Sönke; Mehring, Oliver; Keienburg, Georg; Kengelbach, Jens (Corporate Finance (VHB-JOURQUAL 4 Ranking C))
Unternehmen, die regelmäßig ihr Geschäftsfeldportfolio durch aktives M&A-Geschäft in Form von Verkäufen und Käufen steuern, erzielen deutlich bessere Ein- und Zweijahresrenditen für Aktionäre als alternative M&A-Strategien. Ursächlich hierfür ist u.a., dass die bekannten Effekte in Form von Abschlägen für z.B. diversifizierende Transaktionen oder Stock-Deals deutlich geringer ausfallen als bei Vergleichsgruppen wie z.B. One-Time-Deal Unternehmen. Dieser Beitrag analysiert die Gründe für den Erfolg von Portfoliomastern, Unternehmen die mehr als vier Deals in fünf Jahren durchführen. Durch ein professionalisiertes M&A-Management grenzen sie sich positiv in ihrer mittel- und langfristigen Renditeentwicklung gegenüber Strategic-Shiftern (zwei bis vier Deals) und One-Timern ab. Ihr Erfolg beruht darauf sowohl bei diversifizierenden als auch Stock-Deals bekannte übliche Performanceabschläge zu vermeiden und auch in volatilen Markphasen wertschaffende Deals umzusetzen.
Keywords: M&A; Erfolgsfaktoren; Transaktionsanzahl; Diversifizierung; Volatilität; Cash-Deals; Stock-Deals; Portfoliomaster

Bank funding stability, pricing strategies and the guidance of depositors - Schlueter, Tobias; Sievers, Sönke; Hartmann-Wendels, Thomas (Journal of Banking & Finance (VHB-JOURQUAL 4 Ranking A))
Banks face a 'behavioralization' of their balance sheets since deposit funding increasingly consists of non-maturing deposits with uncertain cash flows exposing banks to asset liability (ALM) risk. Thus, this study examines the behavior of banks’ retail customers regarding non-maturing deposits. Our unique sample comprises the contract and cash flow data for 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior and thus bank funding. The probability of an early deposit withdrawal decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for banks using pricing incentives to steer desired saving patterns for their non-maturing deposit portfolios. Finally, these results are informative regarding the bank liquidity regulations (Basel III) concerning the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC).
Keywords: retail saving behavior; non-maturing deposits; deposit funding; contractual rewards; interest rate bonus; saving persistence; cash flow volatility

Extended dividend, cash flow, and residual income valuation models: Accounting for deviations from ideal conditions - Heinrichs, Nicolas; Hess, Dieter; Homburg, Carsten; Lorenz, Michael; Sievers, Sönke (Contemporary Accounting Research (VHB-JOURQUAL 4 Ranking A+))
Standard equity valuation approaches (i.e., DDM, RIM, and DCF model) are derived under the assumption of ideal conditions, such as infinite payoffs and clean surplus accounting. Because these conditions are hardly ever met, we extend the standard approaches, based on the fundamental principle of financial statement articulation. The extended models are then tested empirically by employing two sets of forecasts: (1) analyst forecasts provided by Value Line and (2) forecasts generated by cross-sectional regression models. The main result is that our extended models yield considerably smaller valuation errors. Moreover, by construction, identical value estimates are obtained across the extended models. By reestablishing empirical equivalence under non-ideal conditions, our approach provides a benchmark that enables us to quantify the errors resulting from individual deviations from ideal conditions, and thus, to analyze the robustness of the standard approaches. Finally, by providing a level playing field for the different valuation approaches, our findings have implications for other empirical settings, for example, estimating the implied cost of capital.
Keywords: Dividend Discount Model; Residual Income; Discounted Cash Flow; Dirty Surplus; Terminal Value; Valuation Error